PERAN MODAL MANUSIA TERHADAP KINERJA ORGANISASI YANG DIMEDIASI OLEH KREATIVITAS UNIVERSITAS KRISNADWIPAYANA - Sintya Agustin; Fajar Cahyo Utomo (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This study aims to determine the description and influence of human capital, creativity and organizational performance at Krisnadwipayana University. The research method used in this study using quantitative methods can be interpreted as a research method based on the philosophy of positivism. Researchers who use a quantitative approach will test a theory by detailing specific hypotheses, then collect data to support or refute these hypotheses. The approach to be used in this research is a quantitative analysis approach based on statistical information. This study shows that the effect of human capital on creativity has a significant effect, the effect of human capital based on the test results has a significant effect on organizational performance, the effect of creativity based on the test results has a significant effect on organizational performance, and the effect of human capital through creativity does not affect organizational performance. because the existence of creativity as a mediating variable does not make the role of human capital increase in organizational performance.